Efektivitas Metode Card Sort terhadap Hasil Belajar Tajwid Siswa TPQ Masjid Jamiek Pauh Pasar Ambacang - Putri, Vini Aprilia; Wirdati, Wirdati (ALSYS, 2024)
Tajweed is one of the subjects taught at the Qur'an Education Center (TPQ) with the aim of providing students with an understanding of how to properly recite the Qur'an. However, in practice, Tajweed lessons are often difficult for students to grasp, as evidenced by the low learning outcomes. Therefore, one effort to improve students' Tajweed learning outcomes is by implementing the card sort method. The purpose of this study is to determine the effectiveness of using the card sort method on Tajweed learning outcomes among students at TPQ Masjid Jamiek Pauh Pasar Ambacang. This study is a quantitative research employing a pre-experimental one-group pretest-posttest design. The sampling technique used is simple random sampling, with a sample size of 30 students. Data were collected using observation guides and achievement tests, and then analyzed using Microsoft Excel and SPSS 28 software. The results showed that the implementation of the card sort method was well-executed with a percentage of 80.6%, the comparison of students' learning outcomes showed a significance of 0.001, and the effectiveness value was 0.7078. Therefore, it can be concluded that the card sort method has a high effectiveness on students' Tajweed learning outcomes.